The Contribution of Money Arisan in Improving Family Welfare According to the Islamic Economic Perspective: Case Study in West Kayunan District of Karanganyar - Muhamad Subagiyo; Hendri Hermawan Adinugraha; Mualimin Mochammad Sahid (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2024)
An arisan is a group of people or groups of people who collect money regularly at any given time. The research aims to find out the contribution of money in increasing family welfare according to the Islamic economic perspective in West Kayunan. The methods used by the researchers in this study are qualitative methods and interpretative approaches to provide the results of data analysis on the contribution of money and practices of its implementation according to Islamic economic views thoroughly and accurately. Data in this study are primary data and secondary data. To analyze data, researchers use data reduction techniques, data presentation, and conclusion drawings. The results of this study show that arisan conducted by the community in West Kayunan hamlet can have an influence on improving family welfare. So this arisan activity is assessed to considerably contribute to increasing the family's well-being. This is because the funds obtained from such arisan activities can be used for consumer and productive purposes. The practice of the arisan system carried out by the community of the West Kayunan is permitted in Islam because in such arisan, there is no element of deception, fair, transparent, witnessed by the participants and no harm.